2018
DOI: 10.1159/000495550
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 Promotes Cancer Metastasis in Osteosarcoma via Activation of the PI3K-Akt Signaling Pathway

Abstract: Background/Aims: LncRNAs have been reported to be vital regulators of the progression of osteosarcoma, although the underlying mechanisms are not completely understood. Methods: The levels of MALAT1 and miR-129-5p expression were measured using qRT-PCR. Cell growth was determined using the CCK-8 and colony formation assays. Cell migration and invasion were detected using the wound healing and Transwell invasion assays, respectively. Tumor growth was determined with a xenograft model. Results: MALAT1 was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…In OS, MALAT1 modulates RET proto-oncogene expression by sponging miR-129-5p, increasing protein expression downstream of the RET-Akt pathway, and its expression was positively correlated with RET and negatively correlated with miR-129-5p in original OS and in xenografted tumor cells. This shows that MALAT1 act as oncogenic lncRNA in OS by regulating RET via miR-129-5p suppression, thereby activating the PI3K-Akt signaling pathway (112).…”
Section: Role Of Non-coding Rnasmentioning
confidence: 93%
“…In OS, MALAT1 modulates RET proto-oncogene expression by sponging miR-129-5p, increasing protein expression downstream of the RET-Akt pathway, and its expression was positively correlated with RET and negatively correlated with miR-129-5p in original OS and in xenografted tumor cells. This shows that MALAT1 act as oncogenic lncRNA in OS by regulating RET via miR-129-5p suppression, thereby activating the PI3K-Akt signaling pathway (112).…”
Section: Role Of Non-coding Rnasmentioning
confidence: 93%
“…The new regulatory network may shed light on the mechanism of RB progression. There were evidences indicated that MALAT1 promoted tumor progression through phosphatidylinositol-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway in non-small cell lung cancer [27] and osteosarcoma [28]. In the next exploration, we will focus on whether the MALAT1/miR-655-3p/ATAD2-induced RB progression was mediated by PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Epigenetic regulation of miR-129-2 was demonstrated in glioma and lung cancer [25,26]. In contrast, however, miR-129 is also upregulated in several solid tumors and non-cancerous tissues from cancer patients with lymph node metastases [27][28][29].…”
Section: Discussionmentioning
confidence: 99%